IDENTIFYING VOCATIONAL STUDENT’S FAMILIARITY WITH VOCABULARY IN ACADEMIC CONTEXT IN ABSTRACT WRITING - Aji, Satriya Bayu; Lubis, Eka Mutia (PRASASTI: Journal of Linguistics, 2020)
In order to write an abstract that appeals to a broader audience, it is important to understand the vocabulary used in the context. By identifying words used in the abstracts of undergraduate thesis from Politeknik Negeri Batam students and comparing them with those used in other academic writings, this research attempts to show that developing student’s awareness of academic writing genre is critical for their progress. The data were taken from the abstract section of undergraduate thesis of Politeknik Negeri Batam students published in 2018, which were compiled into a corpus. From the corpus, the keywords and word profile would be identified, which could then be compared to other corpora. Two word lists (New General Service List and New Academic Word List) were selected as the level lists in carrying out word profiling during the analysis. The results show that the students lacked the necessary words and had not yet recognized the genre of academic writing.